Imagining the West in Eastern Europe and the Soviet Union - Peteri, György (Series in Russian and East European studies., 2010)
An international group of writers explore conceptualizations of what defined "East" and "West" in Eastern Europe, imperial Russia, and the Soviet Union. The contributors analyze the effects of transnational interactions on ideology, politics, and cultural production.